Learning in simple systems. - Burrell, B.D.; Sahley, C.L. (Current Opinion in Neurobiology, 2001)
Cellular processes that mediate learning and memory show a remarkable level of conservation between vertebrates and invertebrates. Recent studies have shown that learning and memory formation in invertebrates, so-called 'simple systems', involves a highly complex arrangement of cellular pathways. Some pathways contribute to a single stage of memory formation, whereas others impact on multiple stages of memory development. Distinct cellular pathways may also act in series or in parallel during various stages of memory formation.